2019
DOI: 10.1016/j.jad.2019.05.035
|View full text |Cite
|
Sign up to set email alerts
|

First-onset and persistence of suicidal ideation in university students: A one-year follow-up study

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. Highlights •Suicidal ideation is common among firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 96 publications
5
30
0
2
Order By: Relevance
“…However, an additional 328 studies were excluded because they did not meet the inclusion criteria for this review. This process left 79 individual studies eligible for inclusion 24 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 ,…”
Section: Resultsmentioning
confidence: 99%
“…However, an additional 328 studies were excluded because they did not meet the inclusion criteria for this review. This process left 79 individual studies eligible for inclusion 24 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 ,…”
Section: Resultsmentioning
confidence: 99%
“…25 A recent study of Spanish university students reported comparable 12-month prevalence and persistence of suicidal ideation; with a mood disorder diagnosis increasing risk and a higher sense of university membership having a protective effect. 29 Peaks in student suicides have been associated with exam periods and winter months, 11 which is relevant to our study as outcome data were collected just prior to final exams in March.…”
Section: Discussionmentioning
confidence: 99%
“…first-year university students (Blasco et al, 2019). Marked changes in lifestyle and social relationships after university/ college admission, in addition to substantial study burden, may affect ASD and ADHD conditions.…”
Section: Discussionmentioning
confidence: 99%